The Molecular Mechanisms of Ferroptosis and Its Role in Blood-Brain Barrier Dysfunction - Chen, Xiaoshu; Pang, Xinru; Yeo, Abrey J.; Xie, Siwen; Xiang, Mengting; Shi, Bin; Yu, Gongchang; Li, Chao (Frontiers in Cellular Neuroscience, 2022)
The blood-brain barrier (BBB) is a selective, semi-permeable layer of endothelial cells that protects the central nervous system from harmful substances circulating in blood. It is one of the important barriers of the nervous system. BBB dysfunction is an early pathophysiological change observed in nervous system diseases. There are few treatments for BBB dysfunction, so this motivates the review. Ferroptosis is a novel cell death mode caused by iron-mediated lipid peroxidation accumulation, which has recently attracted more attention due to its possible role in nervous system disorders. Studies have shown that lipid peroxidation and iron accumulation are related to the barrier dysfunction, especially the expression of tight junction proteins. Therefore, examination of the relationship between ferroptosis and BBB dysfunction may reveal new targets for the treatment of brain diseases.